Complex regional pain syndrome type II arising from a gunshot wound (GSW) associated with infective endocarditis and aortic valve replacement. (16th October 2018) - Tieppo Francio, Vinicius; Barndt, Brandon; Towery, Chris; Allen, Travis; Davani, Saeid
Abstract : A 34-year-old man with a history of gunshot wound (GSW) to the right upper chest developed secondary aortic valve endocarditis (AVE) and was treated with an artificial valve placement (AVP). Three months after, he presented to an outpatient pain management clinic right arm pain and was diagnosed with complex regional pain syndrome type II (CRPS II). The patient underwent a diagnostic sympathetic ganglion block, before undergoing endoscopic thoracic sympathectomy surgery. Successful outcomes revealed decreased pain, opioid utilisation and improved tolerance to therapy and activities of daily living. To our knowledge, this is the first case reporting CRPS II arising from a GSW complicated by AVE followed by AVP, which emphasises how unforeseen syndromes can arise from the management of seemingly unrelated pathology. This case demonstrates the importance of timely and proper diagnosis of uncharacterised residual pain status post-trauma and differential diagnosis and management of chronic pain syndromes.